Peran Dinas Komunikasi dan Informatika dalam Pengendalian Berita Hoaks di Kota Bandar Lampung - Azkilla Fitratunnisa; Nadirsah Hawari; Angga Natalia (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2026)
This study aims to analyze the role of the Communication and Informatics Departemen (Diskominfo) of Bandar Lampung City in controlling the spread of hoax news in the digital space. This research employs a descriptive qualitative approach using Renee Hobbs’ media literacy theory, which consists of five indicators: access, analyze, evaluate, create, and act. Data were collected through observation, interviews, and documentation. The findings indicate that the role of Diskominfo of Bandar Lampung City in controlling hoaxes has not been fully optimal, as reflected in several key issues. First, in terms of access, the dissemination of official information and hoax clarification has not reached all segments of society evenly. Second, regarding analysis, digital issue monitoring has been conducted but remains constrained by limited human resources. Third, in the evaluation aspect, information verification is carried out through inter-agency coordination; however, it has not yet been supported by standardized and systematic procedures. Fourth, in terms of content creation, clarification and media literacy messages have been produced and disseminated through digital platforms, but they have not been implemented consistently and continuously. Fifth, in the action dimension, media literacy education programs are still incidental and have not been integrated as a long-term preventive strategy. Therefore, comprehensive improvements are needed, including strengthening human resource capacity, enhancing information verification mechanisms, and developing systematic and sustainable media literacy programs to support the creation of a healthy public information ecosystem in Bandar Lampung City.